Synthesis, Spectral Characterization, and Antiproliferative Studies of Mixed Ligand Titanium Complexes of Adamantylamine. (27th February 2014) - Kaushal, Raj; Kumar, Nitesh; Chaudhary, Ashun; Arora, Saroj; Awasthi, Pamita
Abstract : Titanium complexes have been synthesized by the reaction between titanium tetrachloride (TiCl4 ), respective bidentate ligand [4, 4′ -dimethoxy-2, 2′ -bipyridine (bpome), 6, 6′-dimethyl-2, 2′-bipyridine (dpme), 1, 2-diaminocyclohexane (dach), 1, 10-phenanthroline (phen), and benzoylacetone (bzac)], and adamantylamine (ada) in 1 : 2 : 2 molar ratios, respectively. The structure of synthesized complexes was confirmed using elemental analysis, FTIR, UV-visible, 1 H NMR, and mass spectrometry techniques. The nanocrystalline nature of complexes was confirmed by powder XRD study. The complexes were evaluated for cytotoxic potential in HeLa (cervical), C6 (glioma), and CHO (Chinese hamster ovarian) cell lines. The complex E was found to be more effective cytotoxic agent against HeLa cell line with an IC50 value of 4.06 µM. Furthermore, the effect of synthesized complexes was studied on different stages of the cell cycle in CHO cells. All complexes exhibited the dose dependent increase in cytotoxicity. The results have shown an increase in sub-G0 population with increase in concentration which is an indicative measure of apoptosis.